2021
DOI: 10.1177/0308575921991950
|View full text |Cite
|
Sign up to set email alerts
|

Foster caring in an era of COVID-19: the impact on personal self-care

Abstract: COVID-19 has undoubtedly affected all caregivers, including foster carers. Despite the importance of self-care in assuaging the impact of the pandemic, there is a dearth of research on this topic, and virtually nothing specific to this important group. This study uses a retrospective pre/post design to measure the impact of the pandemic on foster carers’ self-care. An invitation to participate in an electronic survey was circulated among carers in a US state and a snowball sample of 1229 compiled. Analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…They found that factors such as gender, race, health and employment status affected self-care, with women, non-white/-Caucasian people, those with poor health and the unemployed reporting less self-care engagement than their peers. Miller and Grise-Owens (2021) also used the SCPS to explore the self-care practices of 1,229 foster carers in the US during the Covid-19 pandemic. Results showed that participants’ engagement with self-care was generally low and further decreased during the pandemic.…”
Section: Self-carementioning
confidence: 99%
See 1 more Smart Citation
“…They found that factors such as gender, race, health and employment status affected self-care, with women, non-white/-Caucasian people, those with poor health and the unemployed reporting less self-care engagement than their peers. Miller and Grise-Owens (2021) also used the SCPS to explore the self-care practices of 1,229 foster carers in the US during the Covid-19 pandemic. Results showed that participants’ engagement with self-care was generally low and further decreased during the pandemic.…”
Section: Self-carementioning
confidence: 99%
“…It is worth noting that this study was conducted within the context of the Covid-19 pandemic. Among the foster carer population specifically, the pandemic has created increased childcare issues, carer distress, fear and financial issues (Whitt-Woosley, Sprang and Eslinger, 2022), all of which create a greater need for regular self-care to maintain wellbeing (Miller and Grise-Owens, 2021). This should be considered when interpreting the findings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These conditions were found to be exasperated by individual parent characteristics, such as being a sole caregiver and experiencing poorer mental health and greater financial insecurities (Miller et al, 2020). Another U.S. study found that foster parents engaged in fewer personal self-care practices since the beginning of the pandemic and that determinants included parental older age, poorer mental health status, and greater financial insecurity (Miller & Grise-Owens, 2021).…”
Section: Covid-19 and Resource Parentsmentioning
confidence: 99%
“…The authors suggest that the foster parents’ stress has ramifications for the children’s care, as it places a strain on their family interactions. A US survey reported that self-care practices significantly decreased among foster parents after the start of the pandemic, notably among those who were not married, employed outside their home, had poor mental and physical health, and were financially unstable (Miller & Grise-Owens, 2021). The strain experienced by foster parents has increased because respite care and other child care services are often nonexistent due to physical distancing measures and ill-health (Caldwell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%